Cyclic diynes by alkyne metathesis - Hellbach, Björn; Gleiter, Rolf; Rominger, Frank (Synthesis, 2003)
The preparation of α,ω-diynes with methyl groups at the termini (11a-i) is described. The methylene groups between the alkyne units vary between n = 12 (a) and n = 4 (i). Ring closing metathesis with Mo(CO)6/CF3C6H4OH yielded the monocyclic alkyne 12a with 11a as starting material, whereas 11b-g yielded the cyclic diynes 13b-g. Detailed structural parameters were obtained for 13b and 13c by X-ray crystallography.
Gesehen am 11.11.2020